Behavioral responses to, and fitness consequences from, an invasive species are life-stage dependent in a threatened native fish. (December 2018) - Brown, Timothy R.; Coleman, Rhys A.; Swearer, Stephen E.; Hale, Robin
Abstract: Native wildlife are impacted by invasive species in numerous ways and will be more vulnerable if they cannot recognize the threat posed by an invader. Impacts, however, are generally assessed for a single life stage and without consideration of behavioral responses. This limits knowledge of the mechanisms underpinning the threats of invaders and the responses that could help or hinder native animals to mitigate this threat. We conducted a series of experiments to examine if the threat of an invader and behavioral responses by a native animal are life-stage dependent. Our focal species were a widespread invasive ( Gambusia holbrooki ) and a threatened native Australian freshwater fish ( Galaxiella pusilla ). We show that the threat of, and behavioral responses to, the invader vary across life-cycle stages. Gambusia holbrooki had different effects on G. pusilla : inhibiting reproduction and consuming larvae but not eating eggs or reducing adult growth and survival. Although larval G. pusilla avoided visual cues from G. holbrooki, native predators and conspecific adults, they did not avoid olfactory cues from G. holbrooki, which is maladaptive considering the predation risk. In addition, adult G. pusilla did not avoid any G. holbrooki cues, providing further evidence of maladaptive behavior. Our study is one of the first comprehensive evaluations of how the threats of an invader to a native species, as well as the responses to this threat, are life-stage dependent. We use our empirical results to develop a general framework for understanding the mechanisms by which invasives threaten native biota, and highlight how this can be used to help assess and mitigate the threat of invaders.